Technologies for E-Services 5th International Workshop, TES 2004, Toronto, Canada, August 29-30, 2004, Revised Selected Papers - Shan, Ming-Chien.; Dayal, Umeshwar; Hsu, Meichun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
The 2004 VLDB workshop on Technologies on E-Services (VLDB-TES 2004) was the ?fth workshop in a series of annual workshops endorsed by the VLDB Conference.Itservedasaforumfortheexchangeofideas,resultsandexperiences in the area of e-services and e-business. VLDB-TES 2004 took place in Toronto, Canada. It featured the presen- tion of 12 regular papers, focused on major aspects of e-business solutions. In addition, the workshop invited 2 industrial speakers to share their vision, insight and experience with the audience. The workshop would not have been a success without help from so many people. Special thanks go to Fabio Casati, who organized the program agenda and the proceedings publication, and Chandra Srivastava, who served as the publicity chair. We also thank the members of the program committee and the additional reviewers for their thorough work, which greatly contributed to the quality of the ?nal program. We hope that the participants found the workshop interesting and stimul- ing, and we thank them for attending the workshop and for contributing to the discussions.
TES 2004 -- Robust Web Services via Interaction Contracts -- When are Two Web Services Compatible? -- Negotiation Support for Web Service Selection -- From Web Service Composition to Megaprogramming -- Using Process Algebra for Web Services: Early Results and Perspectives -- Flexible Coordination of E-Services -- : A Tool for Automatic Composition of e-Services Based on Logics of Programs -- Dynamically Self-Organized Service Composition in Wireless Ad Hoc Networks -- Designing Workflow Views with Flows for Large-Scale Business-to-Business Information Systems -- A Practice in Facilitating Service-Oriented Inter-Enterprise Application Integration -- Discovering and Using Web Services in M-Commerce -- Financial Information Mediation: A Case Study of Standards Integration for Electronic Bill Presentment and Payment Using the COIN Mediation Technology.
Keywords: Computer science; Computer communication systems; Database management; Information storage and retrieval; Computers and civilization; Electrical engineering; Computer Science; Database Management; Information Systems Applications (incl. Internet).; Computer Communication Networks; Information Storage and Retrieval; Computers and Society; Communications Engineering, Networks; Electronic books